The Effect of Pubg Gaming Intensity on Verbal Violence Behavior - Ita Rahmawati; Noortje Anita Kumaat; Himawan Wismanadi (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to analyze the influence of PUBG gaming intensity on verbal violence behaviour in adolescents in Indonesia. In the modern era of the 21st century, technological developments, especially in the video game industry, have influenced social behaviour, especially among the younger generation. With more than 100 million active players in Indonesia, PUBG Mobile is one of the most popular games that has the potential to trigger aggressive behaviour. The research method used is quantitative with an explanatory approach, which tests the relationship between the free variable (PUBG game playing intensity) and the bound variable (verbal violent behaviour). The results of the analysis showed that there was a significant influence between the intensity of playing PUBG games on verbal violence behaviour, with a significance value of 0.000 < 0.05. These findings are in line with the General Aggression Model which states that the more often a person plays violent games, the higher the level of verbal aggression shown. This study concludes that parental supervision and social environment also play an important role in shaping adolescent behaviour. Therefore, prevention and education efforts are needed for the public to reduce the negative impact of online games.